The best American short stories 2002 : (Houghton Mifflin Company, 2002)
This year's Best American Short Stories features a rich mix of voices, from both intriguing new writers and established masters of the form like Michael Chabon, Edwidge Danticat, Richard Ford, Jhumpa Lahiri, and Arthur Miller. The 2002 collection includes stories about everything from illicit love affairs to family, the immigrant experience and badly behaved children -- stories varied in subject but unified in their power and humanity. In the words of this year's guest editor, the best-selling author Sue Miller, "The American short story today [is] healthy and strong . . . These stories arrived in the nick of time . . . to teach me once more what we read fiction for."